Affirming Food Waste Mitigation Practices During Pandemic: A Case Study of Green-grocers in Purwokerto, Indonesia - Nainggolan, Racha Defitri; Romadlon, Fauzan; Ananda, Ridho (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
During the COVID-19 pandemic, people tend to panic buying and hoard food supplies. This can trigger an increase in food waste during the pandemic, especially vegetable food waste. This also happens at the level of traders, especially green-grocer who sell in traditional markets. The behavior of traditional market traders who fail to adapt to food safety standards, poor handling, resulting in the emergence of food waste, especially during the pandemic. This study aims to determine the factors that cause vegetable food waste at the level of green-grocers. The method used is qualitative and quantitative with data collection techniques using questionnaires. The sampling was conducted using random sampling and the gained respondents are 111 green-grocers. Then, Chi-Square test is conducted to test the statistical correlation between green- grocer demographic and their preferences about food waste mitigation. The results show there is a correlation between the preferences of green-grocers related to food waste with their demographics. Furthermore, some traders' activities still cause food waste and some of them also don't know what food waste is and what food safety standards are. The less food safety standards, the greater the potential for food waste generated.